Deconstructive Semiotic Discourse of Profit Sharing: Derridean’s Postmodern Critical Study - Bayu Tri Cahya; Irsad Andriyanto; Irma Suryani Lubis; Dian Palupi Aqim (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2022)
Accounting symbols are interpreted differently by researchers, which has an impact on the understanding of profit-sharing as a symbol in Islamic accounting, which is not the only truth in the Derridean constructive semiotic view. The research aims to: (a) analyze accounting practitioners' and non-accounting practitioners' interpretations of profit-sharing using Derrida's deconstructive semiotics; and (b) execute a deconstructivity semiotics-reading of the text connected to their perception of profit-sharing. This study employs a postmodern approach accompanied by a postmodern critical paradigm (particularly Jacques Derridean's philosophy) based on critical theory assumptions and ideas in order to examine social reality. This study's data analysis employs rhetorical deconstruction with Jacques Derridean philosophy as a reflection of deconstructive reading. The findings showed that deconstructive semiotics analysis captures some realities, including: (a) profit sharing as a guarantee for any profits as well as losses from the outcome of a business that two parties agreed upon; (b) profit sharing as justice, justice for each party's rights and obligations under the business cooperation agreement; (c) profit sharing as an agreement and responsibility, the type of agreement that occurs at the start of the collaboration; and (d) profit sharing as an agreement and responsibility. This study clarifies the various meanings of profit sharing as well as the significance of their reality.==============================================================================================================ABSTRAK - Pembagian Keuntungan Semiotik Dekonstruktif: Studi Kritis Postmodern Derridean. Para peneliti berbeda dalam menafsirkan simbol akuntansi, yang juga berdampak pada interpretasi bagi hasil sebagai simbol dalam akuntansi Islam yang bukan satu-satunya kebenaran dalam pandangan semiotik konstruktif Derridean. Tujuan penelitian ini adalah: (a) untuk memahami interpretasi bagi hasil oleh praktisi akuntansi dan non akuntansi dengan semiotika dekonstruktif Derrida; dan (b) melakukan pembacaan semiotika dekonstruktif tentang teks yang terkait dengan interpretasi mereka terhadap bagi hasil. Penelitian ini menggunakan pendekatan fenomenologis disertai dengan paradigma kritis postmodern (khususnya filsafat Jacques Derridean) berdasarkan asumsi dan keyakinan dari teori kritis dengan melihat realitas sosial. Analisis data dalam penelitian ini menggunakan dekonstruksi retoris dengan filosofi Jacques Derridean sebagai refleksi dari pembacaan dekonstruktif. Hasil penelitian menunjukkan bahwa analisis semiotika dekonstruktif mengungkapkan beberapa realitas yaitu; (a) bagi hasil sebagai jaminan atas setiap keuntungan maupun kerugian dari hasil usaha yang disepakati kedua belah pihak; (b) bagi hasil sebagai suatu keadilan, keadilan atas hak dan kewajiban masing-masing anggota perjanjian kerjasama usaha; (c) bagi hasil sebagai kesepakatan dan tanggung jawab, bentuk kesepakatan yang terjadi pada awal kerjasama dan tanggung jawab atas berjalannya kegiatan kerjasama usaha; dan (d) bagi hasil sebagai konsekuensinya, memberikan konsekuensi keuntungan bisnis dari setiap kebijakan bisnis. Kajian ini memberikan pemahaman tentang beragam interpretasi bagi hasil dan makna di balik realitasnya.